Pure robotic retrocaval ureter repair - Hemal,Ashok k. (2008)
PURPOSE: To demonstrate the feasibility of pure robotic retrocaval ureter repair. MATERIALS AND METHODS: A 33 year old female presented with right loin pain and obstruction on intravenous urography with the classical "fish-hook" appearance. She was counseled on the various methods of repair and elected to have a robot assisted repair. The following steps are performed during a pure robotic retrocaval ureter repair. The patient is placed in a modified flank position, pneumoperitoneum created and ports inserted. The colon is mobilized to expose the retroperitoneal structures: inferior vena cava, right gonadal vein, right ureter, and duodenum. The renal pelvis and ureter are mobilized and the renal pelvis transected. The ureter is transposed anterior to the inferior vena cava and a pyelopyelostomy is performed over a JJ stent. RESULTS: This patient was discharged on postoperative day 3. The catheter and drain tube were removed on day 1. Her JJ stent was removed at 6 weeks postoperatively. The postoperative intravenous urography at 3 months confirmed normal drainage of contrast medium. CONCLUSION: Pure robotic retrocaval ureter is a feasible procedure; however, there does not appear to be any great advantage over pure laparoscopy, apart from the ergonomic ease for the surgeon as well the simpler intracorporeal suturing.